168k views
2 votes
Solve for u.
– 22 = -8u + 6(u-7)
Simplify your answer as much as possible.

User Plaute
by
4.6k points

2 Answers

6 votes

Answer:


\boxed{ \boxed{ \mathrm{ \bold{ \blue{ - 10}}}}}

Explanation:


\mathrm{ - 22 = - 8u + 6(u - 7)}

Distribute 6 through the parentheses


\mathsf{ - 22 = -8u + 6u - 42}

Collect like terms


\mathrm{ - 22 = - 2u - 42}

Swap the sides of the equation


\mathrm{ -2u - 42 = - 22}

Move constant to R.H.S and change it's sign


\mathrm{ - 2u = - 22 + 42}

Calculate


\mathrm{ - 2u = 20}

Divide both sides of the equation by -2


\mathrm{ ( - 2u)/( - 2) = (20)/( - 2) }

Calculate


\mathrm{u = - 10}

Hope I helped!

Best regards!

5 votes

Explanation:

- 22 = -8u + 6(u-7)

-22 = -8u + 6u - 42

8u - 6u = 22 - 42

2u = -20

u = -20/2

u = -10

User Venkatskpi
by
5.3k points